2009
DOI: 10.1111/j.1447-0756.2009.01043.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral hydration therapy in oligohydramnios

Abstract: Acute oral hydration is a noninvasive, easily accessible and cheap intervention, and an effective way of increasing AFI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Ghafarnejad 4 reported that with maternal oral hydration therapy, mean AFI improved from 50.8 to 67.2 mm (p < 0.001) while it increase 3d from 62.3 mm to 74.7 mm in 24 hours in our study.…”
Section: Discussionsupporting
confidence: 49%
“…Ghafarnejad 4 reported that with maternal oral hydration therapy, mean AFI improved from 50.8 to 67.2 mm (p < 0.001) while it increase 3d from 62.3 mm to 74.7 mm in 24 hours in our study.…”
Section: Discussionsupporting
confidence: 49%
“…Of these 16 articles, 8 met the inclusion criteria for the first endpoint [ 15 , 16 , 18 , 20 , 21 , 25 – 27 ], 4 for the second endpoint [ 14 , 18 , 20 , 22 ], 2 for the third endpoint [ 19 , 24 ] and 4 for the fourth endpoint [ 17 , 23 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported data regarding oral hypotonic fluid administration (276 women), [ 15 , 16 , 18 , 20 , 25 , 27 ], three studies [ 18 , 20 , 21 ] reported data regarding intravenous isotonic fluid administration ≥2000ml (126 women) and one study regarding fluid intake <2000ml (20 women)[ 26 ], two studies regarding intravenous hypotonic fluid administration (82 women)[ 18 , 20 ]. The analysis of data regarding Δ variation in AFI index in a cohort of women with diagnosis of IO showed significant differences between the intervention group compared to the no treatment group considering both fixed and random effects.…”
Section: Resultsmentioning
confidence: 99%
“…63 Idiopathic oligohydramnios has been found to be responsive to maternal hydration with no difference in IV versus oral hydration acutely or long term. [64][65][66][67] The effect, however, is short lived without continued efforts at hydration. 68 Oral hydration has been shown to change AFI in pregnancies with isolated gastroschisis.…”
Section: Oligohydramniosmentioning
confidence: 99%